Ảnh hưởng của thu nhận và cung cấp kiến thức đến sự đổi mới: Vai trò trung gian của sáng tạo cá nhân - Nguyễn Kim , Nam; Nguyễn Thị Hằng , Nga (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The objective of this study is to examine the influence of knowledge acquisition and knowledge provision on individual creativity and service innovation in the banking sector. The data was collected through a survey of 268 employees working in the banking sector in Ho Chi Minh City. A Structural Equation Modeling procedure was used to test hypotheses. Results indicate that knowledge acquisition has a positive effect on individual creativity. Individual creativity has a positive effect on service innovation and plays mediating role in the relationship between knowledge provision, acquisition and service innovation. Based on the analysis results, the study provides some implications to increase individual creativity in the banking sector to promote service innovation.
Keywords: Knowledge; Creativity; Innovation; Banking